Runaway electrons during subnanosecond breakdowns in high‐pressure gases. Issue 4 (1st December 2016) - Tarasenko, Victor F.; Lomaev, Mikhail I.; Beloplotov, Dmitry V.; Sorokin, Dmitry A.
Abstract : The parameters of runaway electrons produced in nanosecond high‐voltage discharges in different gases (air, nitrogen, sulphur hexafluoride, krypton, argon, methane, neon, hydrogen, helium) at atmospheric and higher pressure were studied. An optical analysis was also performed to investigate the ionisation dynamics in diffuse discharges in nitrogen and nitrogen‐containing mixtures. At breakdown of a point‐to‐plane gap by nanosecond (≃2 ns) high‐voltage (≃200 kV) pulses of negative voltage polarity and gas pressure above 0.1 MPa, a supershort avalanche electron beam (SAEB) was detected by a collector behind the flat anode. For pressure >0.1 MPa of nitrogen and other gases it is shown that the maximum pressure for SAEB registration decreases with increasing the voltage pulse rise time. Therefore, to detect a SAEB at atmospheric and higher gas pressure, one should use voltage pulses with an amplitude of hundred kilovolts and rise time of ∼1 ns and shorter. The experimental research in the dynamics of optical radiation from the discharge plasma shows that the breakdown in which runaway electrons are produced develops as an ionisation wave.